Patterns and predictors of referrals to allied health services for individuals with Parkinson's disease: A Parkinson's foundation (PF) QII study. (February 2021) - Roberts, Angela C.; Rafferty, Miriam R.; Wu, Samuel S.; Miao, Guanhuong; Cubillos, Fernando; Simuni, Tanya; ,; Marras, Connie; Davis, Tom; Dahodwala, Nabila; Neault, Marilyn; Ramirez-Zamora, Adolfo; et al.
Abstract: Introduction: Rehabilitation therapies are critical for optimizing quality-of-life and daily functions for individuals living with Parkinson's disease (PD). Thus, understanding the patterns of and under what conditions physicians make rehabilitation referrals is important for optimizing care. Method: We analyzed data from 5020 participants (4 countries) collected from 1/3/2016 to 4/20/2018 as part of the Parkinson's Foundation Quality Improvement Initiative (PF QII). Data were analyzed for single discipline and multidiscipline referrals to speech language pathology (SLP), physical therapy (PT), and occupational therapy (OT). Group comparisons (referred vs. not-referred) and regression procedures were implemented to determine demographic and clinical variables that were associated with an increased likelihood of rehabilitation referral. Results: 35.3% of participants were referred to rehabilitation services. Of these, 25.1% received a multidiscipline referral. There was a statistically significant effect of disease stage on both single discipline (χ 2 (2) = 45.1, p <  0.0001) and multidiscipline (χ 2 (2) = 74.2, p <  0.0001) referrals, with higher rates in later stages. Referred vs. not-referred participants differed significantly on a number of variables; however, only falls in the 6-months prior, advanced- and moderate-stage disease, older age, hospital admissions, and higher caregiver burden were associated with an increased likelihood of rehabilitation referral (adjusted odds ratios ≥ 1, Range = 1.08 to 1.62). Conclusions: Despite evidence supporting multidiscipline and proactive rehabilitation in PD, the majority of referrals were made to a single service and may be reactions to falls or advancing disease. Data suggest there may be missed opportunities for optimizing care through proactive rehabilitation interventions. Highlights: Single discipline referrals are more common than multidiscipline referrals in PD. Rehabilitation referrals are made reactively in response to falls and advancing disease. There may be missed opportunities for proactive referrals that address quality of life/function. Speech therapy, occupational therapy, and early stage referrals are especially underutilized.